Small-angle x-ray scattering study of nanocrystalline FeyCu1−y alloys produced by ball milling - Fernández van Raap, Marcela Beatriz (2002)
Small-angle x-ray scattering measurements on ball-milled FeyCu1−y giantmagnetoresistivealloys (0.141 y 0.45) have been performed usingsynchrotron radiation. For samples with different nominal compositions,prepared under exactly the same conditions, the scattered intensity recordedas a function of the wavevector varied systematically. For this reason, thestrong scattering signal was attributed mainly to composition fluctuations inthe crystalline grains. The system was treated as a two-phase model consistingof Fe-rich regions in a homogeneous Cu matrix, with composition-dependentrelative volume fractions. Real-space analysis of the scattering was performedin terms of a volumetric distribution of spherical particles. Results indicatethat the main contribution corresponds to 2 nm scattering objects of welldefineddensity contrast. The invariantQwas calculated to assess the variationsin electron-density contrast as a function of the Fe content in the samples.Calculations based on these results allowed the determination of 0.35 at.% ironconcentration in the iron-rich phase for all the nominal compositions studied.